Koncepcja modlitwy integralnej według Orygenesa - Szram, Mariusz (Verbum Vitae, 2012)
The analysis of nature and structure of Christian prayer in Origen’s treatise De oratione (about 234), presented in this article, shows that this opuscule can be considered as a synthesis of the theory of prayer, but it doesn’t contain its decisive and precise conception. Following St. Paul’s teaching (1 Tm 2:1) Origen distinguishes four kinds of prayer: petition, thanksgiving, propitiation and adoration; but in the same time he is convinced that in practice they can’t be separated, because they form an integral act of prayer. For instance, propitiatory prayer can’t form separate prayer, but it is necessary condition of the preparation to each prayer. Origen’s conception was continued in the Latin Church in 5th century by John Cassian and it became base for the later development of the theology of prayer.